Comportamento dos consumidores de vinhos finos: um estudo de caso na empresa Guatambu estância do vinho - Gonçalves, Vânia Regina Carballo (2013)
This study aimed at identify the profile of consumers of wines produced in the Campaign Gaucha and their most relevant preferences. Consumer behavior is closely linked to the final result in the organization studied, consequentlyidentifying an increase in the volume of their sales. This is a case study on the company Guatambu Estancia Wine and the nature it is a qualitative research, predominantly quantitative at levels of exploratory and descriptive research. For Data collection was utilized the scale List Of Valens that allowed answer what is really important for the wine consumer in the purchase decision process. As a result it is possible to highlight more significant than theincrease in sales turnover can be achieved through marketing programs directed to the items that the consumer values with greater emphasis, since the research ties of friendship was most exalted by interviewees regardless of gender, age, education level and family Marketing research has enabled a sense of the complexity of this issue and what is more important, in choosing the product that pleases the consumer is that each day is more demanding and more complete information requests about the wine chosen for consumption. According to the survey, the consumer of fine wines takes into account the price factor, grape variety and brand values the region of origin, awards won and if the grapes are produced in an environmentally proper manner. Having access to this information on the label is crucial from the point of view of the consumer. This research enables the organization to establish one more property marketing orientation more objective and directed to its consumer according to results because it gives pleasure to drink wine tastings and considers the most attractive to discover new flavors. Based on the search results specific actions marketing Guatambu Wine Estancia result in a closer relationship with your consumer.